Investigating crosstalk in lipid rafts between the glucocorticoid receptor and gonadotropin-releasing hormone receptor signaling pathways in a gonadotrope cell line - Wehmeyer, Lance (Department of Molecular and Cell Biology, 2015)
Includes abstract.